Exploring the interplay of prolactin and bromocriptine on serum markers in granulomatous lobular mastitis - Liu, Binheng; Qu, Wenchao; Feng, Yi; Wu, Xueqing; Feng, Jiamei; Gao, Qingqian; Shao, Shijun; Sun, Jiaye; Wan, Hua; Chen, Weiping (Frontiers in Immunology, 2025)
ObjectiveIn this study, we retrospectively analyzed the relationship between PRL level and serum inflammatory and immune markers in patients with granulomatous lobular mastitis (GLM) and analyzed the effect of bromocriptine treatment on serum inflammatory and immune markers in patients with GLM. These analyses were conducted to illustrate that PRL is not only an endocrine hormone but also an immune factor, thereby providing evidence that GLM is an autoimmune disease.MethodsWe conducted a retrospective analysis of GLM cases admitted between 2023 and 2024. Clinical features were compared between patients with differential prolactin (PRL) levels using nonparametric tests, with concomitant documentation of prevalent clinical manifestations. Spearman’s rank correlation was employed to assess associations between PRL concentrations and clinical characteristics/serum biomarkers. To evaluate bromocriptine’s therapeutic efficacy, a propensity score-matched (PSM) cohort was established. Longitudinal serological changes were analyzed using nonparametric statistical methods for paired comparisons.ResultsElevated prolactin levels significantly correlated with lesion size (p<0.05). Patients with abnormal PRL exhibited lower 6-month cure rates compared to those with normal levels (93.1% vs. 100%, p=0.02). Baseline-PRL positively associated with neutrophil counts (NE#), Immunoglobulin E (IgE), and ceruloplasmin (CER) (all p<0.05). After treatment, baseline-PRL remained linked to elevated neutrophils, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), T4 lymphocyte percentage (CD4+ T cells), and IgE, but inversely correlated with lymphocytes (all p<0.05). Propensity-matched analysis (17 bromocriptine-treated vs. 13 no-treated) revealed reduced ESR, downregulated major histocompatibility complex class II (MHC-II) expression, and increased interleukin 4 (IL4), interleukin 5 (IL5), and regulatory T cell percentage (Treg%) levels in the treatment group (all p<0.05).ConclusionsOur findings suggest prolactin may act as an immunomodulatory factor in GLM, potentially influencing T/B-cell immunity and inflammatory cytokine recruitment. Additionally, the observed correlation between prolactin and ceruloplasmin positions ceruloplasmin as a candidate biomarker for GLM, though further validation in independent cohorts is required.